AN ANALYSIS OF FIGURATIVE LANGUAGE EXPRESSIONS IN ONLINE SHOP ADVERTISEMENTS - Jui Lasri Mamonto; Sarah Kamagi; Yapi Wongkar (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims at identifying figurative expressions, their types and meaning in online advertisements. This research applied descriptive method. The subject of this research was advertisements phrases and sentences in online shop advertisements especially that released in Youtube. Based on the findings, It can be concluded that in advertisements, figurative languages are contained. There are various types such as hyperbole, metonimy, metaphor and simile found in online advertisements especially those are accessible in Youtube social platform in video-based database. Each kind of figurative language has different frequency as discovered. Hyperbole has in 15 data (75%), simile has 1 data (5%), metaphor is found in 2 data (10%) and metonimy has 2 data (10%). It is seen that hyperbole has the highest frequency and simile becomes the lowest. Persuasive sentences in online ads are sentences that aim to convince and persuade the reader or listener to carry out the idea expressed in the sentence about something. In making advertisements, people also have to use this type of persuasive sentence because so that readers or listeners feel persuaded to accept the offers in the advertisement. It is a must to pay attention to the use of language which is very important for the success of advertisements in the eyes of the public. The language used in advertisements must be able to be a presentation to the public so that they are interested in something being advertised. It is a must to pay attention to the use of language which is very important for the success of advertisements in the eyes of the public. The language used in advertisements must be able to be a presentation to the public so that they are interested in something being advertised